(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
Tragulids are the best represented ruminants in the Hasnot outcrops of the Pakistani Middle Siwaliks (Late Miocene). The remains described in this paper comprises predominantly isolated teeth, maxilla and mandible fragments. The specimens can be referred to three taxa, namely Dorcatherium minus, Dorcatherium majus and Dorcabune anthracotherioides. The collection of Dorcatherium fossils from Hasnot is the most extensive record of this genus in the Siwaliks. The tragulids suggest a humid habitat with abundant cover.